Studi Lapang: Penegakan Diagnosis Infectious Bursal Disease (IBD) Pada Ayam Broiler - Aan Awaludin; Yudhi Ratna Nugraheni; Theo Mahiseta Syahniar; Dyah Laksito Rukmi; Agus Hadi Prayitno; Nurkholis Nurkholis (Jurnal Ilmu Peternakan Terapan, 2019)
Infectious Bursal Disease (IBD), also called Gumboro, was disease which attacked cells in the bursa of fabricius, causing interference with the chicken's immune system or immunosuppressive. IBD was the one of viral disease that often attacks chickens in the field. The aim of this study was to determine the diagnosis of IBD by through at clinical symptoms and necropsy that can still be relevant on in the field. The diagnosis of IBD correctly, cheaply, easily and quickly in the field is very important to optimize the health care management and evaluation program. The method used was by observing clinical symptoms of broiler chickens in commercial farms suspected of contracting IBD and observing post-death organs (necropsy). The object of necropsy was 5 samples of broiler chickens from the farm. Data was analyzed descriptively. The results of this study was the broiler chickens that infected with IBD could be diagnosed through clinical symptoms and post-death organ changes, so that the diagnosis for IBD cases in the field used the observation of clinical symptoms and necropsy are still relevant.